Approaches to Asthma Diagnosis in Children and Adults - Saglani, Sejal; Menzie-Gow, Andrew N. (Frontiers in Pediatrics, 2019)
Although the hallmark features of asthma include reversible airflow obstruction, airway eosinophilia and symptoms of recurrent wheeze associated with breathlessness and cough, it is accepted as being a heterogeneous disease. The extent of the pathophysiological abnormalities are variable between patients. Despite this, until recently, asthma diagnosis had been made very simplistically predominantly from a clinical history and examination, and often a trial of medication such as short acting bronchodilators. The limitations of this approach have become increasingly apparent with evidence of inappropriate over diagnosis, under diagnosis and misdiagnosis. Although there is no gold standard single test to make a diagnosis of asthma, there are several objective tests that can be used to help support the diagnosis. These include physiological measures such as demonstration of obstructive spirometry associated with reversibility following bronchodilator, and evidence of airway hyperresponsiveness. In addition, we now have non-invasive tests of airway inflammation and are particularly important to identify those with an allergic or eosinophilic phenotype. These tests include measurement of exhaled nitric oxide, or peripheral blood eosinophils. Diagnostic guidelines now reflect the importance of using objective tests to support a diagnosis of asthma, however practical application in the clinic may not be straightforward. The focus of this review is to discuss the advantages and limitations of undertaking objective tests of lung function and airway inflammation in the clinic. In addition, the difficulties related to training and interpretation of the results will be explored and their utility and relevance in adults and children with be compared.